Changes in enamel surface after use of nanoencapsulated fluoride for dental caries remineralization: an in vitro study (Research, Society and Development, 2022)
Aim: To evaluate through an in vitro study surface changes on decayed enamel after the use of fluoridated dentifrices involving nanoencapsulated technology (NanoF). Methods: Forty blocks of human enamel were distributed among four groups (n = 10): 50% NanoF + 50% NaF (50% nF), 100% NanoF (100% nF), 100% NaF as the positive control (PC) and without fluoride as the negative control (NC). The specimens were subjected to a pH cycling model for 7 days. Surface microhardness (SMH), linear surface roughness (Ra) and area surface roughness (Sa) were measured before and after the carious lesion formation and at the end of the treatment. Percentages of surface microhardness recovery (%SMHR), altered Ra (%RaC) and altered Sa (%SaC) were calculated. The data were analyzed using the ANOVA test, repeated-measures ANOVA and Pearson's correlation test (p0.05). Ra and Sa increased after treatment. A significant correlation was found between Ra and Sa. The PC dentifrice had the highest %SMHR, followed by 100% nF (p